THE IMPORTANCE OF EDUCATING YOUNG PEOPLE IN THE SPIRIT OF MILITARY PATRIOTISM (British Journal of Global Ecology and Sustainable Development, 2023)
In this article, today the youth in the spirit of patriotism upbringing was thought about its relevance, importance and unique qualities.